1972
DOI: 10.1063/1.1654112
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe Electroluminescent Device Exhibiting Switching and Memory

Abstract: An MIS structure, in which the semiconductor is suitably doped ZnSe, exhibits switching and memory properties. The same structure also emits light in both forward and reverse bias with an emission wavelength characteristic of the impurities present. Although the operation of the device is not completely understood the switching can be attributed to a transfer of charge from deep impurities in the semiconductor to the insulating layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[5][6][7][8][9][10][11] Suitably doped ZnSe is reported to exhibit switching properties and memory characteristics. 12) The application of ZnSe nanocrystals embedded in poly[(2-methoxy,5-octoxy)-1,4phenylenevinylene] (MOPPV) in designing hybrid photovoltaic devices has been introduced by Yun et al 13) Nitrogen-doped graphene=ZnSe nanocomposites have been reported to have enhanced electrochemical performance and find potential applications in fuel cells, energy storage, and nanodevices. 14) Recently, attention has been focused on the PVA-ZnSe films.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Suitably doped ZnSe is reported to exhibit switching properties and memory characteristics. 12) The application of ZnSe nanocrystals embedded in poly[(2-methoxy,5-octoxy)-1,4phenylenevinylene] (MOPPV) in designing hybrid photovoltaic devices has been introduced by Yun et al 13) Nitrogen-doped graphene=ZnSe nanocomposites have been reported to have enhanced electrochemical performance and find potential applications in fuel cells, energy storage, and nanodevices. 14) Recently, attention has been focused on the PVA-ZnSe films.…”
Section: Introductionmentioning
confidence: 99%